Studi Kasus Stuttering Pada Anak Usia Dini - Novita Alya Ananti; Ahmad Fauzan Al Ghifari; Lucky Purwantini (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2024)
Stuttering is a disorder in language or speech in which a person is difficult or difficult to speak clearly and smoothly and someone who experiences stuttering or stuttering tends to extend or repeat a syllable. This research aims to explore more deeply the case of stuttering in early childhood. In addition, this study aims to find out the causes or factors that cause stuttering in the subject and find out what treatments have been done to cure the subject from stuttering. In this study, researchers used a qualitative research design with a case study method. The subject in this study is a boy with the initials ABA where the subject is 8 years old and the sampling technique in this study uses non-probability using purposive sampling. From the results of the research conducted, it was found that the subject often lengthened the consonant and vowel sounds. The subject also does not speak fluently or intermittently on several consonant letters, namely “B, G, and M”. The cause of stuttering in the subject is due to the neglect of the subject's parents since birth who are rarely involved in the subject's learning process.